EFEKTIVITAS PENGGUNAAN METODE BELAJAR TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KOMPETENSI PENATAAN SANGGUL DAERAH CIWIDEY DI SMK NEGERI 1 LAMONGAN - Retno Astuti; Dewi Lutfiati; Nia Kusstianti; Sri Dwiyanti (Jurnal Tata Rias, 2024)
The insufficient involvement of students in the academic process affect their academic performance. Therefore, peer tutoring method is selected to foster students to engage more proactively in the educational process by having them serve as peer trainers. The intent of this research is to examine the impact of peer tutoring method on student activeness, improves learning outcomes, and how students respond to the use of this method. The study employs a quantitative approach with 26 twelfth-grade students as the research subjects. The data were obtained through observation, learning outcome tests, and questionnaires, with data analysis involving mean calculations, paired sample t-tests, and one-sample t-tests. The findings of the study are as follows: 1) Student activeness received an average score of 3.57, indicating a "very good" level of engagement. 2) Analysis of learning outcomes revealed a significant distinction, with a calculated t-value of 12.640 exceeding the critical t-value of 2.06, reflecting an increase of 24.04. A one-sample t-test yielded a calculated t-value of 5.734, , also greater than the critical t-value of 2.06, confirming that the average psychomotor score of 80.88 surpassed the minimum competency criterion of 75. 3) Student responses, with an average score of 3.34, were classified as "very good." These evidence shows that the peer tutoring method is effective in enhancing learning outcomes in the study of traditional Ciwidey hairstyles at SMK Negeri 1 Lamongan. Keywords: Peer Tutoring Methods, Learning Outcomes, Ciwidey Traditional Hairstyling.